Vpliv vaje kratko stopalo na vzdolžni stopalni lok pri triatloncih - Mav, Primož (Šport (Ljubljana), 2020)
Frequent training in sports, where running and jumping are dominant, put a great strain on the foot. As a result, athletes who engage in such sports often have problems with the longitudinal foot arch. Movement and stability of the longitudinal foot arch are controlled by larger global muscles and smaller local foot muscles. Researches shows that short-foot exercises improve the performance of local foot muscles in an average physically active population. The purpose of the present study was to determine whether short-foot exercise affects the navicular bone drop in static and dynamic conditions in triathletes. The study involved nine triathletes (age 14.6 +- 2.8 years, weight 50.3 +- 10.5 kg and height 164.9 +- 14.5 cm). Before starting and after six weeks of exercise, the subjects performed a sit-standing navicular bone drop test (SSNDT) and a dynamic navicular drop test (DND). Absolute values in millimeters SSNDT and DND were analyzed, all for the left foot. The comparison of pre- and post-exercise results was made by ANOVA for repeated measurements. The results showed that the arithmetic mean of the absolute value of SSNDT of the left foot decreased significantly by 56% after exercise (p <0.001). The arithmetic mean of the absolute DND value also decreased statistically significantly (34%; p <0.05). Based on our research, it can be concluded that a six-week short-foot exercise improves the performance of the longitudinal foot arch and reduces foot pronation for triathletes in static and dynamic conditions.
Keywords: kratko stopalo; longitudinal foot arch; short-foot; sport; stopalni lok; šport; training; trening; triathlon; triatlon